The experience of loneliness at work during the COVID-19 pandemic: a study in the Higher Education Sector - Frost, Fiona (2020)
Loneliness is a complex and multi-faceted concept which is experienced by individuals in different ways. This qualitative study explores sentiments of loneliness at work amongst 35 staff members at the University of Nottingham during the COVID-19 pandemic through the use of interpretive phenomenological analysis (IPA). Existing definitions of loneliness from a philosophical understanding and a social psychology perspective are explored and the subjectivity of loneliness is discussed.